The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0113135
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Primary Psychopathy, but Not Physical Formidability or Attractiveness, Predicts Conversational Dominance in a Zero-Acquaintance Situation

Abstract: The determinants of conversational dominance are not well understood. We used videotaped triadic interactions among unacquainted same-sex American college students to test predictions drawn from the theoretical distinction between dominance and prestige as modes of human status competition. Specifically, we investigated the effects of physical formidability, facial attractiveness, social status, and self-reported subclinical psychopathy on quantitative (proportion of words produced), participatory (interruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Previous research has suggested that psychopathy and narcissism (but not Machiavellianism) are associated with strive for dominance (Rauthmann & Kolar, 2013), which could be a reason why these traits linked with gossip (McAndrew et al, 2007). Interestingly, a recent study found that individuals high in primary psychopathy had high levels of conversational dominance (i.e., greater number of words during a conversation; Manson, Gervais, Fessler, & Kline, 2014). It is possible that having multiple conversation topics facilitates the agentic, competitive inter-personal orientation typical to individuals high in psychopathy and narcissism (Rauthmann & Kolar, 2013), explaining why these traits were associated with more diverse gossip motivations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that psychopathy and narcissism (but not Machiavellianism) are associated with strive for dominance (Rauthmann & Kolar, 2013), which could be a reason why these traits linked with gossip (McAndrew et al, 2007). Interestingly, a recent study found that individuals high in primary psychopathy had high levels of conversational dominance (i.e., greater number of words during a conversation; Manson, Gervais, Fessler, & Kline, 2014). It is possible that having multiple conversation topics facilitates the agentic, competitive inter-personal orientation typical to individuals high in psychopathy and narcissism (Rauthmann & Kolar, 2013), explaining why these traits were associated with more diverse gossip motivations.…”
Section: Discussionmentioning
confidence: 99%
“…Those high in dominance are also likely to cue social formidability and are more inclined to speak and attempt to forcefully direct group-related tasks. For example, dominant individuals are prone to deepen their voice during initial interaction, speak with force and subtly tease or ostracize others to produce fear (Bendersky & Hays, 2011;Brass & Burkhardt, 1993;Case & Maner, 2014;Cheng, Tracy, Ho, & Henrich, 2016;Keltner, Young, Heerey, Oemig, & Monarch, 1998;Manson, Gervais, Fessler, & Kline, 2014). Through these behaviors, the individuals who become more conversationally domineering and interrupt during task-related conversations are perceived higher in dominance and, in turn, higher in social rank in groups of unacquainted individuals (Cheng, Tracy, Foulsham, Kingstone, & Henrich, 2013;Farley, 2008).…”
Section: The Longitudinal Dynamics Of Social Hierarchymentioning
confidence: 99%
“…Because shallow emotions comprise one aspect of psychopathy [ 1 , 2 ], it is possible that individuals high in psychopathic traits do not provide enough behavioral material to give highly empathetic individuals an advantage in judging their psychopathy levels based on thin slices. As tentative support for this speculation, among our target individuals, analysis using the Linguistic Inquiry and Word Count application [ 59 ] showed that F1 LSRP was negatively associated with the use of affect words, after controlling for sex [ 34 ]. Perhaps the negative effect of EQ on judgment accuracy in the silent video condition occurred because of the condition’s induced focus on non-verbal emotional cues.…”
Section: Discussionmentioning
confidence: 95%
“…Second, our theoretical framework relied on the distinction between psychopathy’s underlying propensity toward exploitative behavior and its superficial “mask of sanity” [ 1 ], but the LSRP-LORP, unlike the Psychopathic Personality Inventory [ 61 ], does not distinguish between these sub-traits. However, target individuals higher in LSRP F1 tended to dominate triadic conversations [ 34 ], suggesting that LSRP F1 captures some of the same variation captured by the PPI’s Fearless Dominance scale, which is hypothesized to represent the “mask” ([ 62 ] but see [ 63 ]). Third, we did not collect information on judges’ ages or ethnicities, limiting our ability to test adaptive error management hypotheses of psychopathy detection, particularly in view of our findings regarding the effects of targets’ ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation